Estimation of Carbon Stock in The Seagrass Meadows of Jelenga Bay, West Sumbawa, Indonesia - HIZRIAN IRDA (nim : 10613018), MUHAMMAD
Blue carbon is a term used to describe the carbon stored in coastal and marine ecosystems. Research and conservation of blue carbon sinks like seagrass meadows are important in the effort to mitigate global climate change. This research aimed to estimate blue carbon stored in the seagrass meadow ecosystem of Jelenga Bay, West Sumbawa, Indonesia. The carbon pools studied include aboveground biomass, belowground biomass, and substrate. Carbon stock in the seagrass community was estimated based on correlation of density, biomass, and organic carbon content. Seagrass density was measured from 45 plots measuring 0.5 m ÃƒÂ— 0.5 m, in which seagrass biomass for each species was hand collected. Carbon stock in substrate was estimated using the correlation of its dry bulk density and organic carbon content. Substrate samples were taken at five depths (0-15 cm, 15-30 cm, 30-50 cm, 50-70 cm, and 70-100 cm) using a modified soil corer measuring 1.5 m in length and 2.5 cm in diameter. Seagrass biomass and substrate organic carbon content were analyzed using the Walkley and Black method. Four seagrass species were found in Jelenga Bay, i.e., Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, and Halodule pinifolia. Based on Landsat 8 OLI image analysis, Jelenga Bay has 107.1 hectares of seagrass meadow area. Carbon stock estimation of the seagrass community within that area showed that aboveground seagrass biomass stores as much as 19.1 Mg of carbon, whereas belowground biomass stores as much as 28.4 Mg of carbon. Enhalus acoroides contributes the highest amount of total carbon stock in the seagrass community, i.e., as much as 26.9 Mg (56.7%). Carbon stock estimation in seagrass substrate shows that it stores as much as 45.5 Mg of carbon. Substrate at 70-100 cm depth contributes the highest amount of carbon stock compared to other depths, i.e., as much as 14.9 Mg (32.5%).